Influence of Storage Media Type and Duration on the Viability of Longan Seeds (Dimocarpus longan L.) - Moch. Ari baha'udin; Nova Triani; Sutini (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Longan fruit is in high demand; however, longan plants produce recalcitrant seeds, which are less resistant to drying and contain higher moisture levels than orthodox seeds. Recalcitrant seeds typically remain viable for only 3–5 days if not stored under optimal conditions. This study aimed to determine the optimal combination of organic storage media and storage duration for maintaining longan seed viability. The first factor was the type of organic storage medium (sawdust, cocopeat, and rice husk charcoal), and the second was the storage duration (7, 14, 21, and 28 days). The parameters observed included germination power, sprout length, sprout weight, maximum growth potential, and sprout root length. A Completely Randomized Design (CRD) was employed, and the data were analyzed using ANOVA. When significant effects were detected, a post-hoc BNJ test at the 5% level was conducted. The analysis revealed no significant interaction between storage media type and duration on any parameter. The storage medium had no significant effect, whereas storage duration significantly affected germination power, sprout length, and sprout weight, but not maximum growth potential or root length. Seeds stored for 7 days performed better than those stored for 28 days. Control seeds (without storage) exhibited the best overall results. This study suggests that longan seeds can be stored for up to 7 days while maintaining optimal viability, which is useful for seed distribution and commercial cultivation.